2008
DOI: 10.1089/bfm.2007.0011
|View full text |Cite
|
Sign up to set email alerts
|

Physician-Led Outpatient Breastfeeding Medicine Clinics in the United States

Abstract: Attrition of exclusive breastfeeding is highest during the first 3 months postpartum. Timely management of breastfeeding in the outpatient setting through innovative models of healthcare delivery may increase its duration and exclusivity. Our goal was to examine the structure and function of physician-led clinics in the United States that specialize in providing outpatient clinical support for breastfeeding-related issues ("breastfeeding medicine clinics"). We posted a survey on Listservs of the American Acade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Few studies of breastfeeding clinics in industrialized countries have been identified [ 10 - 17 ]. These clinics aim to increase breastfeeding duration and diminish the prevalence of difficulties [ 10 , 11 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Few studies of breastfeeding clinics in industrialized countries have been identified [ 10 - 17 ]. These clinics aim to increase breastfeeding duration and diminish the prevalence of difficulties [ 10 , 11 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our participants pieced together their own training curricula from existing literature and webinars; evidence-based methodologies and protocols were not part of their training. This practice was confirmed by Shaikh and Smillie (2008), who also have reported that the majority of surveyed physicians in breastfeeding clinics are educated via materials sought as a result of their own curiosity. Furthermore, Edwards and colleagues (2015) have suggested that frontline practitioners utilize free and convenient online resources, because time limitations, regional access, and financial limitations serve as barriers to formal continuing education.…”
Section: Discussionmentioning
confidence: 62%
“…Two other studies in the United States were survey based and therefore not as rigorous in their methodology as the randomized intervention trials. Shaikh and Smillie [46] found through a self-reported survey of clinic based lead physicians (N = 13 clinics responded ) that while there was a growth of membership in the Academy of Breastfeeding Medicine there appeared to be no explicit educational program. Clinics used in house educational programs as well as materials provided by La Leche League International, The American Academy of Pediatrics and teaching hospitals.…”
Section: North Americamentioning
confidence: 99%